1999
DOI: 10.1021/ac9903048
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Enhanced Flow System for High-Temperature Digestion of Resistant Organic Materials

Abstract: Microwave-assisted flow digestion systems open up newpossibilities in fully automated sample preparation for element analysis. For an extensive and fast oxidation of organic materials with nitric acid, temperatures of more than 200 °C are necessary. To achieve the desired temperatures of ∼250 °C, it is essential that the pressure in the system can be increased up to 35 bar. The teflon tubes used, however, do not withstand the vapor pressure of the digestion mixture at these temperature levels. A high-pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…When performed in closed vessels analyte losses and contamination are avoided, a fast and efficient digestion is promoted and reagent consumption and waste generation is reduced. Based on the applied pressure during digestion, they can be broadly classied as ambient pressure, 5-9 medium pressure (<25 bar) [10][11][12] or high pressure (>25 bar) [13][14][15] ow digestion systems. These procedures are time consuming anddespite the fast heating stepadd signicantly to the total time required for the digestion step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When performed in closed vessels analyte losses and contamination are avoided, a fast and efficient digestion is promoted and reagent consumption and waste generation is reduced. Based on the applied pressure during digestion, they can be broadly classied as ambient pressure, 5-9 medium pressure (<25 bar) [10][11][12] or high pressure (>25 bar) [13][14][15] ow digestion systems. These procedures are time consuming anddespite the fast heating stepadd signicantly to the total time required for the digestion step.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these steps are very difficult to automate, making manual operation mandatory. 17 Pichler et al 13 used a PTFE tube to form an inert reactor for sample decomposition. Moreover, ow digestion systems can be easily interfaced to techniques for analyte quantication (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…16 A subsequent design avoided the need for the nitrogen bomb and enabled direct introduction of solid samples, through which fresh extractant was continuously pumped, and connection to a subsequent step of the analytical process. The highly complex first design required solid samples to be slurried and the assistance of a nitrogen bomb to supply N 2 at a constant pressure up to 5 bar.…”
Section: Dynamic Mae High Pressurementioning
confidence: 99%
“…The sample throughput is given to be 6 samples/h. PICHLER et al [133] have shown that such an on-line microwave procedure can also be adapted to pressurized ashing. In this special case, the sample is injected into a constant stream of nitric acid which passes the microwave heating zone.…”
Section: Automation and Direct Analysis 281 Automationmentioning
confidence: 99%